Peran Metode Cerita Islami dalam Menanamkan Moral Keagamaan Mata Pelajaran Akidah Akhlak di Kelas III MI Model Panyabungan, Mandailing Natal, Sumatera Utara - Putri Amaliya LBS; Endri Yenti; Al Baihaqi Anas (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This article investigates how Islamic tales might be used to teach moral lessons to young children. The research hinges on the idea that Islamic storytellers can effectively teach religious morals to primary school students by using relatable, real-world examples. class absences, class lists, class decisions, and classes that will be awarded are just some of the activities carried out by MI educators in the Panyabungan Model. Researchers play integral roles throughout the entire process, from ideation to implementation to data collecting and analysis and finally report writing, in this method of conducting qualitative research. Methods of information gathering that include keeping detailed notes and conducting interviews. Secondary statistics come from the documentation of Grade III A in the MI Model of Cooperative Education, while primary data come from teachers and students in that grade. According to the results of this research, there is a multi-step process involved in integrating the Islamic storytelling technique into the third-year curriculum of Akidah Akhlak at the MI Model Panyabungan. First and foremost, a person's upbringing, environment, and access to educational materials can all strengthen or weaken Islamic worldviews. First, Michigan's school system Each Panyabunga model has spent countless hours working with infants and toddlers, gaining invaluable knowledge along the way. Both sets of kids have religious backgrounds and were encouraged by their parents to get an education. Books, the Internet, and audiobooks are three of the most accessible educational resources for teachers. However, time, classroom management, and storytelling tools are three areas where Islamic storytelling falls short.